Demographics, laboratory parameters and outcomes of 1061 patients with coronavirus disease 2019: a report from Tehran, Iran. (November 2020) - Pourabdollah Toutkaboni, M.; Askari, E.; Khalili, N.; Tabarsi, P.; Jamaati, H.; Velayati, A.A.; Dorudinia, A.; Rezaei, M.; Nadji, S.A.; Mohamadnia, A.; Khalili, N.
Abstract: We aimed to determine the characteristics of coronavirus disease 2019 (COVID-2019) among the Iranian population. In this study, we collected and analysed the demographics, laboratory findings and outcomes of patients with COVID-19 who were admitted to Masih Daneshvari Hospital in Tehran, Iran between 20 February 2020 and 2 April 2020. Among 1061 patients, 692 (65.2%) were male and the median age was 55 years (interquartile range (IQR), 44–66 years). Totally, 129 (12.2%) patients died during hospitalization in the ward or intensive care unit. From the remaining 932 individuals, 46 (5.0%) were admitted to the intensive care unit and 886 (95.0%) were hospitalized in the ward. Those patients who died were significantly older than those hospitalized in the ward (p < 0.001). The median absolute number of lymphocytes was 1.2 × 10 3 /μL (IQR 0.9 × 10 3 to 1.6 × 10 3 /μL) and 708 (66.7%) patients had lymphopenia (absolute lymphocyte count <1500/μL). Among the laboratory tests, D-dimer, serum ferritin and albumin had the strongest correlations with mortality (r = 0.455, r = 0.412, r = –0.406, respectively; p < 0.001 for each one). In conclusion, laboratory findings could provide useful information with regard to the management of individuals with COVID-19.